Infectious conjunctivitis - Meghpara, Beeran (Henry Stewart Talks, 2020)
Bacterial conjunctivitis: less common than viral conjunctivitis in adults, Treatment of bacterial conjunctivas: often started empirically, Topical antibiotics should not be used to treat viral conjunctivitis, Hyperacute gonococcal conjunctivitis can progress rapidly to involve the cornea: systemic treatment is essential, Chlamydial conjunctivitis causes a chronic follicular conjunctivitis that is treated with systemic medication, Blepharoconjunctivitis: a chronic conjunctivitis that requires concomitant treatment of the eyelids